Understanding Standardization and Variation in Mediterranean Ceramics - European Association of Archaeologists. Annual meeting (Leuven ; Paris ; Walpole)
vii, 196 sayfa
Keywords: “ This volume is designed as a wide-ranging analysis of ceramic standardization and variation, and as a contribution to pottery studies in the Mediterranean and beyond. It originates in a conference session at the 16th Annual Meeting of the European Association of Archaeologists which was held in The Hague, The Netherlands, and was organized by the research team of the project New Perspectives on Ancient Pottery (NPAP) of the Amsterdam Archaeological Centre, University of Amsterdam. Some of the most enduring questions archaeologists raise are explicitly or implicitly formulated around the concepts of standardization and variation. Yet, the significance of these concepts has rarely been acknowledged in archaeological literature and their full potential for the study of ancient culture remains under-explored. To demonstrate the significance of these concepts for the study of material culture, we adopt here a cross-cultural and diachronic perspective. The individual chapters cover a variety of case studies, ranging from Spanish handmade pottery to John Beazley's Greek vase painters. The range of approaches pursued is equally broad and involves traditional stylistic analyses, applications of archaeological science, statistical methodologies, and post-processual considerations. The result will hopefully stimulate pottery experts and specialists in other categories of artifacts to revisit their material from different and fresh angles.” --